P14.64 Primary Central Nervous System Lymphoma (PCNSL) with HD- MTX based chemotherapy: tolerability and results. (6th September 2019) - Silvani, A; Anghileri, E; Simonetti, G; Eoli, M; Finocchiaro, G; Pollo, B; Farinotti, M; Fariselli, L; Gaviani, P
Abstract: BACKGROUND: Primary Central nervous system (CNS) lymphomas (PCNSL) are extranodal, malignant non- Hodgkin lymphomas of the diff use large B-cell type, confined to CNS. It accounts for up to 1% of all lymphomas and about 3% of all CNS tumours. The incidence continues to rise in immuno- competent elderly patients.Although the prognosis of PCNSL remains poor, it has improved in the past two decades as a result of better treatment strategies. However, treatment recommendations still result mainly from retrospective series or single-arm phase 2 studies and a few three completed randomised trials. We described a series of patients with newly diagnosis of PCNSL treated with modified-schedula published by Omuro MATERIAL AND METHODS: Patients was treated with HD-MTX, procarbazine, vincristine, received four 28-day cycles of chemotherapy, on schedule: HD-MTX (3·5 g/m²) days 1 and 15; Procarbazine (100 mg/m²) on days 1–7. Vincristine (1·4 mg/m²) on days 1 and 15. Toxicity was assessed with Common Terminology Criteria for Adverse Events version 4. The International PCNSL Collaborative Group Response Criteria were used for response assessment. Endpoints include overall survival (OS) and adverse events (AE). RESULTS: 21 immunocompetent patients (12 females and 9 males) were retrospectively studied, among 2014 to 2019. Median age at diagnosis 61 years (range 41–76). Median KPS at diagnosis was 70 (range 40–100). Clinical and radiological data and treatment related toxicity were described CONCLUSION: Present combination regimen is effective; however, AE incidence is high, and often induces schedule modification